Breast Reconstruction Using Tram Flap: Prospective Outcome and Complications - Homayoon Zehtab; Hamid R.Fathi; Ebrahim Hatamipour; Mehdi Fathi (Medical Journal of The Islamic Republic of Iran, 2006)
Background:The transverse rectus abdominis musculocutaneous TRAM) flap remains the gold standard for postmastectomy reconstruction either immediate or delayed.However,transfer of TRAM flap can be associated with donor site morbidities and complications in flap.A successful reconstruction consists of careful patient selection, surgical technique and meticulous preoperative planning.This study was designed to evaluate outcome and complications of breast reconstruction with TRAM flap in association with patient conditions and risk factors, prospectively. Methods: Breast reconstruction was performed in 44 women consecutively,using the TRAM flap during a 3-year period, 1999–2002. Modified radical mastectomy accompanying immediate reconstructions with TRAM flap was performed for 12 patients and delayed reconstruction was used for other patients with previous mastectomy. Results: The mean age of the patients was 40.41±4.43 years. Thirty (68.18%) patients had comorbidities, consisting of radiation therapy, obesity, hypertension, diabetes mellitus, smoking and abdominal scar. Contralateral and ipsilateral TRAM flaps were used in 26(59.09%) and 14(31.81%) reconstructions, respectively. The abdominal defect was repaired in layers with the use of synthetic mesh in 30(68.18%) patients. The overall complication rate was 31.82%, such as fat necrosis (15.91%), partial flap loss (13.64%), etc. Satisfaction rates were excellent in 10 (22.72%), good in 25 (56.82%), moderate in five (11.36%), and poor in four (9.09%) patients. The mean of postoperative inpatient hospital days were 15.18±4.89 and 14.28±6.52 in patients with contralateral and ipsilateral flaps,respectively (p>0.05).A significant association was observed between overall complications and comorbidities. Partial flap loss and fat necrosis was associated with smoking, and abdominal hernia was associated with obesity marginally.Conclusions:The outcome of breast reconstruction using TRAM flap is similar by surgical technique and time of reconstruction.The most common flap complications were fat necrosis and partial flap loss that was associated with smoking. Acceptable satisfaction is obtained by TRAM flap.